Moralized Health-Related Persuasion Undermines Social Cohesion - Täuber, Susanne (Frontiers in Psychology, 2018)
Integrating theory and research on persuasion, moralization, and intergroup relations, the present research aims to highlight the far-reaching impact of health-related persuasion on society. I propose that governments’ health-related persuasion leads to the emergence of new social norms, and in particular moral norms. Importantly, moral norms provide strong behavioral imperatives and are seen as binding for group members. This suggests that moralized persuasion has a strong potential to divide society along the lines of citizens who conform to and citizens who deviate from health-related moral norms. Thus, departing from the traditional focus on targets of persuasion, the present research focuses on those holding a moralized view on health and lifestyle. Key aspects of social cohesion as defined by the OECD (2011) have been tested across four studies. The key hypothesis tested is that those conforming to the norm (e.g., non-smokers, normal weight people, people with healthy lifestyles) will stigmatize those deviating from the norm (e.g., smokers, overweight people, people with unhealthy lifestyles). Flowing from stigmatization, less inclusion, lower solidarity with and greater endorsement of unequal treatment of those deviating from the moral norm are predicted. Four survey studies (total N=1568) examining the proposed associations among non-smokers, normal weight people, and employees with healthy lifestyles. The studies provide unanimous support for the hypothesis, with meta-analysis providing further support for the reliability of the findings. Consistent across studies, social cohesion indicators were negatively affected by health moralization through stigmatization of those deviating from health-related moral norms. Findings highlight an under-acknowledged potential of moralized health-related persuasion to divide society, thereby undermining cohesion and the achievement of important societal goals. In the discussion, limitations and relevant routes for future research are highlighted. Recommendations are derived for policy makers, institutions, employers, and individuals.